Knowledge, Attitude and Practice Toward Prescribing Antibiotics for Upper Respiratory Tract Infections among Primary Health Care Physicians in Cluster 1 - Abuhekmah, Nouf; AlAlwan, Areej; AlHarbi, Thekra; Alqahtani , Amwaj; Swaralzahab , Mazin (International Journal of Innovative Research in Medical Science, 2022)
Background: Respiratory tract infections are among the most frequently encountered clinical conditions and upper respiratory tract infections (URTIs) are one of the most common reasons for consultations in primary health care centers. Antibiotics are often prescribed unnecessarily for URTIs around the globe. Identifying factors associated with the ubiquitous inappropriate prescribing of antibiotics for URTIs will help develop effective interventions and decrease antimicrobial resistance. The Aim of study to find out the resources of physicians' knowledge regarding upper respiratory tract infection management, to identify the clinical factors that might affect antibiotics prescription by primary health care physician. Methodology: This is cross sectional observational quantitative study was carried out at Primary health care centres during the period from January to august 2021 in Cluster-1 Riyadh, Saudi Arabia. An online self-administered questionnaire was conducted on 197 physicians by using convenient sampling technique. The data was analysed using SPSS software version 23. The study was done on all physicians who work in primary health care in cluster 1 for one year and more, male and female, Saudi and non-Saudi, include consultants, specialists, residentsand general practitioners. Results: In this study, we were able to collect 197 responses of our questionnaire with mean age of 31.6 years old (SD= 6.27). More than half of the participants were males (54.8 %) and 72.6 % of them were residents. Furthermore, 91.9 % of the participants reported following of criteria or guideline for prescribing of antibiotics in treatment of UTRI. Among those physicians, 88.4 % of them reported depending on centorcriteria. Furthermore, 70.6 % of the physicians reported a frequency of patients request of antibiotic of 1-4 times during the past months and 44.7 % of them would not accept to the patients request while 28.9 % would refuse and educate the patients and 21.3 % would agree according to guidelines. Conclusion: We found good to moderate level of knowledge among the physicians toward the use of antibiotics in treatment of URTI however, some improvement in the patient’s knowledge should be considered.